2004
DOI: 10.1029/2004ja010651
|View full text |Cite
|
Sign up to set email alerts
|

Subionospheric early VLF signal perturbations observed in one‐to‐one association with sprites

Abstract: [1] Observations on the night of 21 July 2003 of the ionospheric effects of a thunderstorm in central France are reported. From 0200 to 0315 UT, a camera system in the Pyrenees Mountains captured 28 sprites, triggered by +CG lightning as observed by the French METEORAGE lightning detection system. A narrowband VLF receiver located on Crete, at $2200 km southeast of the storm, observed subionospheric VLF signals from six ground-based transmitters. The amplitude of one of the VLF signals, originating at a transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
98
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 21 publications
12
98
2
Order By: Relevance
“…It is now believed that sprites in the lower ionosphere associate closely with early/fast VLF perturbations, although these perturbations may not be unique to them. This relation was hinted by early measurements over the United States, reported by Inan et al (1996b) and Dowden et al (1996), while more recent observations in Europe, reported by Haldoupis et al (2004) and Mika et al (2005), suggested a nearly one-to-one relationship.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is now believed that sprites in the lower ionosphere associate closely with early/fast VLF perturbations, although these perturbations may not be unique to them. This relation was hinted by early measurements over the United States, reported by Inan et al (1996b) and Dowden et al (1996), while more recent observations in Europe, reported by Haldoupis et al (2004) and Mika et al (2005), suggested a nearly one-to-one relationship.…”
Section: Introductionmentioning
confidence: 86%
“…The perturbation magnitudes varied from 0.15 to 0.3 dB and the onset durations (i.e. the time needed for the maximum perturbation to be reached) were in the range of 20 ms−2 s, including both early/fast and early/slow (e.g., see Haldoupis et al, 2004) type events, while the relaxation times were ∼2−3min. Example perturbations accompanying the elve event discussed previously in Fig.…”
Section: Eurosprite2003 Elvesmentioning
confidence: 99%
“…Armstrong (1983) rst reported the VLF perturbations that occurred within 100 ms (i.e., within the time resolution of the instrument) of the causative lightning discharges, which were thus termed "early" or "early/fast" events by Inan et al (1988). Early VLF events are caused by scattering from the localized regions of the conductivity enhancements in the lower ionosphere associated with lightnings, producing Transient Luminous Events (TLEs) such as sprites, halos and elves (e.g., Dowden et al, 1994;Inan et al, 1996a;Sampath et al, 2000;Rodger, 2003;Haldoupis et al, 2004;Mika et al, 2005Mika et al, , 2006Marshall et al, 2006;Kumar et al, 2008;Inan et al, 2010). However, from a comparison of early/fast VLF events with sprite observations in the USA on three dates (during 1995-2000) with high sprite activity, it was concluded that early/fast VLF events and sprites were not well correlated as many sprites occurred even without any early/fast event and vice versa .…”
Section: Introductionmentioning
confidence: 99%
“…[2] VLF remote sensing is a sensitive technique to detect transient disturbances of the nighttime lower ionosphere ($40 to 90 km altitude), resulting from high energy auroral precipitation [e.g., Potemra and Rosenbert, 1973;Cummer et al, 1997], lightning-induced electron precipitation [e.g., Inan and Carpenter 1987], electromagnetic and quasielectrostatic coupling produced by lightning discharges (e.g., sprites and elves) Moore et al, 2003;Haldoupis et al, 2004;Cheng and Cummer, 2005], cosmic gamma-ray bursts (GRBs) [Fishman and Inan, 1988], and g-ray flares from a magnetar [Inan et al, 1999]. VLF detection of daytime ionospheric disturbances is less common, but include solar X-ray flares [Mitra, 1974].…”
Section: Introductionmentioning
confidence: 99%